SHERIF KHIMSHIASHVILI — ARCHITECT OF PEACEFUL INTEGRATION - Nugzar Zosidze; Nadim Varshanidze; Ana Varshanidze; Mirian Putkaradze (International Journal of Innovative Technologies in Social Science, 2025)
The presented scientific work is dedicated to an in-depth analysis of the political figure of Sherif Khimshiashvili and an assessment of his strategic actions in the historical context of the second half of the 19th century. The authors present him as an example of transformational leadership, whose political vision and moral authority became a decisive factor in the peaceful return of Adjara to its historical homeland - Mother Georgia..Historians explore how Sherif Khimshiashvili, relying on dynastic tradition, inherited responsibility, and a sense of political intuition, was able to guide regional transition without violence. He is portrayed not as a passive feudal lord but as an active intermediary between external empires and the local society. His strategy was rooted in internal legitimacy, negotiation-focused politics, and cultural compatibility, which enabled the peaceful navigation of a potentially conflict-ridden transformation.The paper is based on discourse-contextual analysis, integrating historical sources with contemporary theoretical approaches, including leadership theory, memory politics, and the concept of transitional justice. The authors argue that Sherif Khimshiashvili's actions may be interpreted as a realization of national self-consciousness that transcended the circumstantial role of the ruling class and exemplified moral leadership during the imperial age.Khimshiashvili’s political strategy established a legitimate basis for the integration of Adjara with the Georgian state—a process that remains a relevant lesson for modern Georgia, especially in a time when reconciling regional identities with national unity continues to be a challenge. His legacy, which combines feudal tradition, national vision, and peaceful diplomacy, deserves greater recognition in both Georgia’s collective historical memory and its contemporary political thought.